Elastomer modification by means of ionizing radiation - Bobrova, Valeryia; Andrei, Kasperovich; Vladimir, Mozyrev; Krmela, Jan; Krmelová, Vladimíra (Institute of Physics Publishing Ltd, 2020)
One of the priorities for improving the performance characteristics of elastomer compositions is their physical modification, which allows to obtain materials with a new set of performance properties. Among the known methods of modifying products based on elastomers, one of the actual methods is radiation modification. It allows you to control the physicomechanical and elastic-strength characteristics of products. In connection with the foregoing, the development of a technology for the radiation modification of elastomers with the aim of increasing their operational characteristics is relevant. In this work, the effect of ionizing radiation on the thermo-physical and operational properties of elastomeric compositions for the tread of career tires was investigated. It was established that the level of the maximum temperature developed in the samples depends on the degree of vulcanization of the elastomeric compositions. In samples of tread rubber, heat generation is reduced by 2–4 % after treatment with accelerated electrons. In the process of exposure to ionizing radiation, the formation of free radicals and their subsequent recombination occurs. Revealed an increase in crosslinking density in modified specimens. The correlation dependences between the thermophysical properties ofelastomeric compositions and the intensity of heat generation in them are established. It was determined that the best thermo-physical properties of polymers with a degree of crosslinking t80. The wear resistance of the modified elastomeric compositions is increased up to 3.5 times.
Modifikace elastomerů pomocí ionizujícího záření
Keywords: elastomer; radiation modification; thermo-physical properties; elastomer; modifikace zářením; termofyzikální vlastnosti